Acute ischemic stroke in COVID-19: a case report - Ramalingaiah, Mamatha Tittamegalapalya; Jogihalli Mood, Jeetendra Kumar; Murthy, Vinutha Bagalur Srinivas; Singh, Virender (International Journal of Advances in Medicine, 2021)
Corona virus disease (COVID-19) is an infectious disease caused by SARS-CoV-2 virus. It predominantly affects respiratory system causing fever, cough, and breathlessness. But it can also affect central nervous system. Clinicians must adopt methodical approach in investigating a patient with neurological manifestation. Early detection and treatment is required for neurological disease of COVID-19 to reduce post COVID neurological sequel.